RANCANGAN SISTEM KEAMANAN GUDANG BERBASIS MIKROKONTROLER MENGGUNAKAN SENSOR PASSIVE INFRA RED (PIR) PADA TOKO CITRA BUSANA JAMBI - Darex Susanto (JURNAL AKADEMIKA)
Development of Information Technology at this time is very fast and rapidly, so that it can providebenefits for the community to live a daily life in which, at this time humans require to do everything quickly effective and efisen, for that we must meminimalisirkan Cost and time appeal done manually such as for example in the control apparatus or electronic devices as well as in at Implement the Security System (Security System). Sensor IR (Infra Red) and Ultrasonic is an automatic sensor with a range long enough.